2011
DOI: 10.1007/s11864-011-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targeted Therapies and Vaccination Strategies for Mesothelioma

Abstract: Novel targeted therapies have found a niche in the treatment of many cancers, although the most responsive populations, best biomarkers of response, and appropriate treatment settings are still under investigation. With few exceptions, cancer vaccination strategies have not entered into routine management. In malignant mesothelioma, combination first-line chemotherapy with a platinum and pemetrexed remains the standard of care when systemic therapy is considered. Second-line chemotherapy is used but benefits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The development of clinical interventions based on vaccines have been limited so far from the lack of ubiquitous shared antigens in MM. Wilms' tumor‐1 (WT‐1) antigen is the only candidate antigen that has been targeted by vaccination in MM patients . The fact that MM cells and tissues from different sources consistently express survivin and MHC‐I suggested that a vaccination against survivin may be beneficial for the vast majority of MM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of clinical interventions based on vaccines have been limited so far from the lack of ubiquitous shared antigens in MM. Wilms' tumor‐1 (WT‐1) antigen is the only candidate antigen that has been targeted by vaccination in MM patients . The fact that MM cells and tissues from different sources consistently express survivin and MHC‐I suggested that a vaccination against survivin may be beneficial for the vast majority of MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wilms' tumor-1 (WT-1) antigen is the only candidate antigen that has been targeted by vaccination in MM patients. 31 The fact that MM cells and tissues from different sources consistently express survivin and MHC-I suggested that a vaccination against survivin may be beneficial for the vast majority of MM patients. In the case of WT-1 vaccination, synthetic peptides were used to generated CD4 1 and CD8 1 responses.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence suggests that the immune system plays a critical role in protection against MPM [5,94,95]. TILs play an important role in anti tumor immune responses by recognizing tumor-specific antigens and T-cell infiltration has already been associated with a good prognosis in many cancers, such as ovarian and colon cancer.…”
Section: Immune Checkpoints In Mesothelioma: a New Treatment Opportunmentioning
confidence: 99%
“…The incidence of MPM is still expected to increase over the next decades due to the long latency between exposure to asbestos and diagnosis and because asbestos is still being used in developing countries [4]. The prognosis of MPM patients remains poor with a median overall survival time in untreated patients of about 10 months and a 5 year survival rate of less than 5% [4,5]. Palliative platinum-antifolate chemotherapy is the only treatment with proven improvement of outcome in MPM, resulting in a median survival of about 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant pleural mesothelioma (MPM) is an aggressive tumour of the pleural cavity with dismal prognosis . Given the poor benefit provided by currently used therapies, research efforts have focused on molecules and pathways that can be specifically targeted for therapeutic purposes . Mechanistic target of rapamycin (mTOR) which has been implicated in cell proliferation, survival, metabolism, migration and angiogenesis is activated in the majority of MPM and has been linked to worse prognosis .…”
Section: Introductionmentioning
confidence: 99%